Soil Salinity: Causes and Impacts on Agriculture and the Environment - Kreba, Sleem Ali Saleem (Journal of agricultural, environmental and veterinary sciences, 2019)
Soil salinity is an important issue for agriculture and the environment, especially in arid and semi-arid regions. Soil salinity influences agricultural productivity and soil properties. It is strongly related to irrigation and groundwater. This review article considers collecting published scientific knowledge about the soil salinity issue. It considers introducing the soil salinity, its types, its causes, its impacts on agriculture and the environment, its measuring methods, and its reclamation methods. The article considers also the remote sensing technology and its use in monitoring and predicting soil salinity. This article was prepared to help farmers, students, scientists, and researchers in agricultural and environmental sectors. Conserving affected lands with salinity is costly and time consuming, and choosing the right crops and plant species is the most important method to deal with this issue.
Keywords: soil salinity; electric conductivity; adsorbed and exchangeable sodium; soil properties; remote sensing technology